Eighteenth International Seaweed Symposium
DOI: 10.1007/978-1-4020-5670-3_29
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthesis and UV-B tolerance of the marine alga Fucus vesiculosus at different sea water salinities

Abstract: The marine algal species in the Baltic Sea are few due to the low sea water salinity. One of the few species that can be found is Fucus vesiculosus. Even this species is affected by the low salinity and becomes smaller in size in the Baltic. In present work the photosynthesis of F. vesiculosus in the northern Baltic (Bothnian Sea) was compared to the photosynthesis of F. vesiculosus in the Atlantic. Oxygen evolution was measured before and after exposure to 2.3 W of UV-B (280-320 nm) radiation for 5 h, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
16
2

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 14 publications
3
16
2
Order By: Relevance
“…Faster electron transfer rate in the Baltic algae, in turn, would disagree with the data showing faster oxygen evolution in the Atlantic ecotype (Bäck et al. 1992, Nygård and Ekelund 2006). Thus, we conclude that the strong PSII fluorescence in the Bothnian Sea ecotype of F. vesiculosus reflects better ability of PSII to harvest the blue excitation light used in the fluorescence measurements, rather than a high PSII/PSI ratio.…”
contrasting
confidence: 64%
See 3 more Smart Citations
“…Faster electron transfer rate in the Baltic algae, in turn, would disagree with the data showing faster oxygen evolution in the Atlantic ecotype (Bäck et al. 1992, Nygård and Ekelund 2006). Thus, we conclude that the strong PSII fluorescence in the Bothnian Sea ecotype of F. vesiculosus reflects better ability of PSII to harvest the blue excitation light used in the fluorescence measurements, rather than a high PSII/PSI ratio.…”
contrasting
confidence: 64%
“…Nygård and Ekelund (2006), however, measured higher chl a and c concentrations in the Norwegian Sea ecotype from samples collected in January. The chl a / c ratios of Nygård and Ekelund (2006) were higher than those measured in the present study (Table 2), 18 for the Baltic Sea ecotype of F. vesiculosus and 24 for the Norwegian Sea ecotype. These data indicate that light‐harvesting complexes of Fucus decrease during winter but increase in May.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Lower levels of Chl a were partly responsible for the lower light absorption capacity observed for type D corals in this study (which was identified by a less acute initial slope, α, in the RLCs) but did not fully explain the 38% lower α when normalized to cellular Chl a . Some alternative explanations may be that, compared with type C2, type D symbionts may have smaller or fewer photosynthetic units for capturing incident light (Nygård & Ekelund 2006), fewer PSII reaction centres or PQ molecules (Honti 2007), or that there are differences in the optical properties of the host tissue. Alternatively, type D symbionts may divert more of the incident light energy to ATP production via cyclic phosphorylation through the Mehler cycle (Raven 1976), which does not result in the evolution of oxygen or the fixation of carbon (McCabe‐Reynolds et al.…”
Section: Resultsmentioning
confidence: 99%